2016
DOI: 10.3389/fnbeh.2016.00084
|View full text |Cite
|
Sign up to set email alerts
|

Profound and Sexually Dimorphic Effects of Clinically-Relevant Low Dose Scatter Irradiation on the Brain and Behavior

Abstract: Irradiated cells can signal damage and distress to both close and distant neighbors that have not been directly exposed to the radiation (naïve bystanders). While studies have shown that such bystander effects occur in the shielded brain of animals upon body irradiation, their mechanism remains unexplored. Observed effects may be caused by some blood-borne factors; however they may also be explained, at least in part, by very small direct doses received by the brain that result from scatter or leakage. In orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Role of DNA methylation in BMP4 regulation in tumor brain and chemo brain needs to be further substantiated in the large-scale studies. Here, we noted the downregulation of the neurotrophic factors pathway, which was previously reported to be downregulated by chemotherapy agents and radiation [ 14 , 33 ], and may therefore constitute biomarkers of brain toxicity. In the future, to gain a full understanding of pathways and processes affected in tumor brain and chemo brain, it would be important to conduct a detailed analysis of the brain signalome and entire interactome, using novel platforms such as OncoFinder and iPANDA [ 34 , 35 ] that allow an in-depth analysis of entire signalome in context of different diseases and conditions [ 36 40 ].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Role of DNA methylation in BMP4 regulation in tumor brain and chemo brain needs to be further substantiated in the large-scale studies. Here, we noted the downregulation of the neurotrophic factors pathway, which was previously reported to be downregulated by chemotherapy agents and radiation [ 14 , 33 ], and may therefore constitute biomarkers of brain toxicity. In the future, to gain a full understanding of pathways and processes affected in tumor brain and chemo brain, it would be important to conduct a detailed analysis of the brain signalome and entire interactome, using novel platforms such as OncoFinder and iPANDA [ 34 , 35 ] that allow an in-depth analysis of entire signalome in context of different diseases and conditions [ 36 40 ].…”
Section: Discussionmentioning
confidence: 71%
“…Western immunoblotting was conducted as previously described [ 14 , 33 , 76 ]. In brief, around 50 mg of PFC tissues were sonicated in ice-cold 1% SDS and immediately boiled.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, this present study has analyzed radiation effects in male mice. Recent studies have shown that radiation effects are, in fact, more profound in females than in males [ 64 , 65 ]. Therefore, it would be prudent to analyze the effects of fractionated, low-dose radiation as a function of animal sex.…”
Section: Discussionmentioning
confidence: 99%
“…Western immunoblotting was carried out as previously described (Silasi et al, 2004 ; Kovalchuk et al, 2016a , b , c ). In brief, hippocampal tissues were sonicated in ice-cold 1% SDS and immediately boiled.…”
Section: Methodsmentioning
confidence: 99%